2014
DOI: 10.1371/journal.pone.0094932
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of HIV-1 Infection in a General Population of Fishing Communities around Lake Victoria, Uganda

Abstract: BackgroundHigh HIV-1 incidence rates were reported among persons in fisherfolk communities (FFC) in Uganda who were selected for high risk behaviour. We assessed the incidence of HIV-1 and associated risk factors in a general population FFC to determine population-wide HIV rates.MethodsA community-based cohort study was conducted among a random sample of 2191 participants aged 18–49 years. At baseline and 12 months post-baseline, data were collected on socio-demographic characteristics and risky behaviors (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 27 publications
(44 reference statements)
9
119
2
Order By: Relevance
“…12,20 The findings of this study support the implementation of a communication strategy that would teach communities about discordance and encourage all couples to have couple HIV testing. Lessons from Uganda could help inform other countries with generalized HIV epidemics.…”
Section: Accuracy Of Knowledge Of Hiv Status Of Sexual Partnermentioning
confidence: 52%
“…12,20 The findings of this study support the implementation of a communication strategy that would teach communities about discordance and encourage all couples to have couple HIV testing. Lessons from Uganda could help inform other countries with generalized HIV epidemics.…”
Section: Accuracy Of Knowledge Of Hiv Status Of Sexual Partnermentioning
confidence: 52%
“…Globally, research has found high levels of substance abuse, multiple sex partners, and transactional sex among fisherfolk [1, 6-14]. Moreover, fisherfolk have underutilized antiretroviral treatment (ART), as compared with other subgroups [15, 16], in part due to their high mobility (they follow fish populations around the lake) and irregular work schedules; they are frequently far from healthcare, not consistently near the same clinic, and not available during clinic hours [1, 8, 10, 17-21]. Such underutilization of ART can lead to a higher likelihood of HIV transmission, if infected [22].…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study in Beijing observed overall HIV incidence in 449 MSM at 8.6 (95% CI: 6.7–11.0) per 100 PY [7]. Men who reported exclusively sex with men were more likely to be at higher risk of HIV than men who reported sex with men and women [8]. However, interpretation of these rates must be cautious as such assays have previously found to over-estimate HIV incidence due to persons falsely testing as recently infected [9].…”
Section: Introductionmentioning
confidence: 99%